VARK Learning Modalities Score and GPA of First Year College Students - Sutanto, Nadia; Lasmono, Hari K.; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2011)
The goal of this study was to reveal whether there is a difference in VARK learning modalities score between first year psychology and pharnacy college students, whether a difference exists based on gender, and whether there is a relation between the VARK learning modalities score with the grade point average (GPA). This study recruites 464 first year college students (278 subjects from the faculty of pharmacy and 186 subjects from the faculty of psychology) as subjects in the population study. The test of difference on VARK modalities score between faculties and gender didn’t show any significant differences (p > .05), aside from the kinesthetic modality. The test of correlation between VARK modalities score and GPA showed that there is a significant positive correlation (p < .05), so it can be concluded that individuals with high VARK modalities total score tend to have high semester GPA. Tujuan studi ini adalah mengungkap apakah ada perbedaan skor modalitas belajar VARK antara mahasiswa baru fakultas psikologi (FPsi) dan farmasi (FFarm), apakah ada beda berdasarkan gender, dan apakah ada hubungan skor modalitas belajar VARK dan indeks prestasi semester (IPS). Penelitian ini melibatkan 464 mahasiswa baru (n FFarm = 278, n FPsi = 186) dengan menggunakan population study. Uji beda skor modalitas VARK berdasarkan perbedaan fakultas dan jenis kelamin tidak menunjukkan adanya perbedaan (p > .05), kecuali modalitas kinestetik. Uji korelasi antara skor modalitas VARK dan IPS menunjukkan adanya korelasi positif yang signifikan (p < .05), sehingga dapat disimpulkan bahwa individu yang memiliki skor total modalitas VARK yang tinggi, cenderung memiliki IPS yang tinggi.